(3TQM OhGhjf GdTYQGA GdSJIs - (3jhSa Hf SdjeGf Hf YjSi GdnqTrfnJneQj GdCfOdSj, CHh GdMLGL GdeYQha HGdCYde,J (B476 (3g` s
(3ChdgG (B:s
(3baGfHc ef PcQi MHjH hefRd HSbW Gddhi Hjf GdONhd aMhed s
(3BNQgG (B:s
(3JHGTjQ Ci ThGgO dG Ydjg hfHTQ Hg hcHQ GdTF eYXeg ced GdSaQ GdChd s
(3GdfSNI HgG MhGTs
(3fSNI KGfjgs
(3hjTJed gPG GdLRA Ydi TQM OhGhjf GeQF GdbjSs
(3hgj GdbUGFO GdeJNjQI ef TYQg eeG Qhi GdWhSi Yf TjhNg s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
Keywords: (3GdCOHs